Logistics customer service: analysis regards to implementation of order processing in Shapadu Kontena Berhad / Abdul Halim N. C. Mohamad - N. C. Mohamad, Abdul Halim (1994)
Shapadu Kontena Berhad has been around for the past 25 years. Shapadu Kontena Berhad matured with age to become one of the most stable and influential Bumiputra Company in the country. Shapadu Kontena Berhad has also grown extensively with branches throughout the country, which offer integrated services.